Chemically synthesized hot melt adhesive and preparation method thereof

By constructing a gradient polymerization system and dynamic viscoelastic regulation process of multifunctional matrix resin, combined with high-pressure dispersion and rapid cooling technology, the shortcomings in the existing chemical synthetic hot melt adhesives in mechanical properties and preparation processes have been solved, and the physical and chemical properties of hot melt adhesives have been significantly improved in the wide temperature range.

CN119875537AInactive Publication Date: 2025-04-25SHENZHEN JINHONGXIN IND DEVELOPMENT CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510185320.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-19
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing chemical synthetic hot melt adhesives have shortcomings in mechanical properties and preparation processes, including mechanical contradictions, low-temperature elongation difference, charge accumulation effect, and difficulty in directed grafting of functional monomers.

Method used

By constructing a gradient polymerization system for multifunctional matrix resins, a dynamic viscoelastic regulation process is developed, and a high-pressure dispersion and rapid cooling technology is combined to optimize the formulation and process flow, including the use of styrene-butyl acrylate-methacrylic acid copolymer as matrix resin, and a three-stage polymerization process controlled by gradient temperature is adopted.

Benefits of technology

It significantly improves the physical and chemical properties of hot melt adhesives in a wide temperature domain, improves the thermal stability of the material and the elongation of the break at low temperatures, and improves the cohesive strength and tensile strength retention rate under high shear conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875537A_ABST
    Figure CN119875537A_ABST
Patent Text Reader

Abstract

The invention discloses a chemically synthesized hot melt adhesive and a preparation method thereof, and the chemically synthesized hot melt adhesive comprises the following components: 400-600 parts of matrix resin which is a vinyl copolymer with hydroxyl or carboxylic acid functional groups; the tackifier is formed by compounding hydrogenated rosin glyceride and terpene resin according to the mass ratio of (1: 0.8)-(1: 1.2); 80-150 parts of a viscosity modifier, which comprises a blend of polyethylene wax containing a branched chain alkyl structure and microcrystalline wax; the antioxidant is formed by compounding a hindered phenol compound and a phosphite ester compound according to the ratio of (1: 2)-(2: 1); the functional additive comprises a synergistic combination of an ultraviolet light absorber and an inorganic filler. The physical and chemical properties of the hot melt adhesive in a wide temperature range are remarkably improved by constructing a gradient polymerization system of multifunctional matrix resin, developing a dynamic viscoelasticity regulation and control process and combining a high-pressure dispersion and rapid cooling technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of adhesives, and more specifically, particularly relates to a chemically synthesized hot melt adhesive. At the same time, the present invention also relates to a preparation method of the chemically synthesized hot melt adhesive. Background Art

[0002] In the field of adhesive technology, chemical synthetic hot melt adhesives have been widely used in packaging, automobiles, electronic devices and other industrial fields due to their solvent-free and fast curing properties. The existing chemical synthetic hot melt adhesives have the following shortcomings:

[0003] Most of them use single ethylene-vinyl acetate (EVA) or polyolefin as the matrix resin, and the functional groups in its molecular chain are unevenly distributed, which leads to mechanical contradictions in the product. Although increasing the melting temperature can enhance the thermal stability, it will significantly deteriorate the elongation at break in low temperature environment;

[0004] Although traditional plasticizer systems (such as paraffin and phthalates) can improve processing fluidity, they will cause charge accumulation effects and accelerate the photo-oxidation aging of materials.

[0005] In terms of preparation, most of them currently use the constant temperature segmentation method, which cannot achieve directional grafting of functional monomers. Differential scanning calorimetry (DSC) analysis shows that the half-peak width of the glass transition temperature of such products is as high as 25-30°C, reflecting that the molecular weight distribution index is too high;

[0006] Based on the above, we propose a chemically synthesized hot melt adhesive and a preparation method thereof, which effectively improves the performance and preparation aspects of the chemically synthesized hot melt adhesive. Summary of the invention

[0007] The purpose of the present invention is to solve the shortcomings existing in the prior art, and to propose a chemically synthesized hot melt adhesive and a preparation method thereof, by constructing a gradient polymerization system of a multifunctional matrix resin, developing a dynamic viscoelasticity control process, and combining high-pressure dispersion and rapid cooling technology, to achieve significant improvement in the physical and chemical properties of the hot melt adhesive in a wide temperature range.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] A chemical synthetic hot melt adhesive, characterized in that: the formula of the chemical synthetic hot melt adhesive consists of the following ingredients:

[0010] 400-600 parts of a base resin, wherein the base resin is a vinyl copolymer with a hydroxyl or carboxylic acid functional group, and the molar ratio of the unsaturated monomer to the functional monomer in the vinyl copolymer is 3:1-5:1;

[0011] 200-350 parts of a tackifier, which is prepared by mixing hydrogenated rosin glycerol ester and terpene resin in a mass ratio of 1:0.8-1:1.2;

[0012] 80-150 parts of a viscosity modifier, comprising a blend of polyethylene wax containing a branched alkyl structure and microcrystalline wax;

[0013] 5-15 parts of an antioxidant, wherein the antioxidant is composed of a hindered phenol and a phosphite compound in a ratio of 1:2-2:1;

[0014] Functional additives 1-3%, including a synergistic combination of ultraviolet absorbers and inorganic fillers, wherein the ultraviolet absorbers are a composite system of hydroxybenzotriazole compounds and nano zinc oxide, and the mass ratio of the two is 1:0.5-1:1.5; the inorganic filler is a layered silicate material surface-treated with a silane coupling agent, and its particle size D50 is 2-5 μm, and the bulk density is 0.3-0.6 g / cm 3 ;

[0015] The modification treatment of the layered silicate material comprises:

[0016] First, proton exchange was performed under acidic conditions of pH 3-4;

[0017] Then, a grafting reaction is carried out with a silane coupling agent containing an epoxy group;

[0018] Finally, high temperature activation treatment is carried out at 450-550°C.

[0019] Preferably, the base resin is styrene-butyl acrylate-methacrylic acid copolymer, wherein:

[0020] The styrene monomer content accounts for 45-60% of the total mass of the copolymer;

[0021] The butyl acrylate content accounts for 25-40% of the total mass of the copolymer;

[0022] The methacrylic acid content accounts for 3-8% of the total mass of the copolymer;

[0023] Its glass transition temperature is -35°C to -20°C.

[0024] Preferably, the synthesis process of the base resin includes:

[0025] The three-stage polymerization process with gradient temperature control is as follows:

[0026] First polymerization stage: bulk polymerization is initiated at 65-75°C;

[0027] The second polymerization stage: heating to 85-90°C for grafting reaction;

[0028] The third polymerization stage: cooling to 70-75°C to complete the directional modification of functional groups.

[0029] Preferably, the synthesis process of the base resin includes: the hydrogenated rosin glycerol ester of the tackifier and the terpene resin:

[0030] The degree of hydrogenation of rosin acid is 85-95%, and the softening point of terpene resin is 105-125°C;

[0031] The composite system of the two exhibits a synergistic viscosity-increasing effect at a shear frequency of 10 rad / s, and the composite viscosity is 1.2-1.8 times that of the single component viscosity.

[0032] A method for preparing a chemically synthesized hot melt adhesive comprises the following steps:

[0033] S1, pre-reaction stage: pre-react the matrix resin raw material with a solvent at 80-100° C. for 30-60 minutes, wherein the solvent is a mixed solvent of ethyl acetate and acetone in a volume ratio of 1:0.5-1:2;

[0034] S2, main copolymerization stage: under nitrogen protection, adding a tackifier and an initiator system in sequence, wherein the initiator system comprises a gradient initiation combination of benzoyl peroxide and azobisisobutyronitrile;

[0035] S3, functional modification stage: adding viscosity modifier three times at 110-130°C, each time with an interval of 15-30 minutes and performing ultrasonic dispersion treatment;

[0036] S4, post-processing stage: liquid nitrogen is used to quickly cool the shape after melt extrusion, and the cooling rate is controlled at 15-25℃ / s;

[0037] Among them, the oxygen content of the whole process of the preparation method of chemical synthetic hot melt adhesive is controlled below 50ppm.

[0038] Preferably, the main copolymerization stage adopts segmented temperature control:

[0039] During the heating stage, the temperature is raised to the reaction temperature at a rate of 5-8°C / min;

[0040] The temperature fluctuation during the constant temperature stage should not exceed ±1°C;

[0041] The cooling stage adopts a gradient cooling mode, including:

[0042] The first cooling stage: cooling to 100℃ at 3-5℃ / min;

[0043] The second cooling stage: cooling down to 80℃ at 1-2℃ / min;

[0044] The liquid nitrogen rapid cooling molding process comprises:

[0045] Initial cooling stage: cool the material to below -30℃ within 3-5 seconds;

[0046] Secondary shaping stage: the particle diameter is controlled in the low temperature pulverizer within the range of 0.5-2mm;

[0047] Balance treatment stage: aging for 12-24 hours at a temperature of 25°C-30°C and a relative humidity of 40-60%.

[0048] Preferably, in step S3, the interval time (Δt) of adding the viscosity modifier each time is determined by the following dynamic equation:

[0049]

[0050] Where η 0 is the initial viscosity of the system (mPa·s), which was measured by rotational rheometer at 100 s -1 Measured at shear rate; η 1 is the real-time dynamic viscosity (mPa·s), collected every 30 seconds by an online viscosity sensor;

[0051] Where, ΔT = Tm-Tc;

[0052] Tm is the set upper limit of process temperature (°C);

[0053] Tc is the current material center temperature (℃);

[0054] K is the process coefficient, with a range of 8.5×10 -3 -1.2×10 -2 ;

[0055] When the calculated value exceeds the 15-30 minute range required by the process, the system automatically adjusts the ultrasonic power to:

[0056]

[0057] Where P 0 is the preset ultrasonic power, γ = 0.15 ± 0.02 is the adjustment gain, τ = (5 ± 0.5) min is the time constant, and the arctan function is limited to the interval [-π / 2, π / 2] to ensure stable output.

[0058] Preferably, the gradient-induced combined addition rate (v) in step S2 is performed according to the following optimization function:

[0059]

[0060] In the formula, v max represents the maximum theoretical addition rate of the initiator, erf is the error function, t 1 / 2is the half-life correction value, ΔH obs is the heat release monitored in real time, ΔH thr is the theoretical threshold, δ is the activation buffer value, C is the catalytic transfer coefficient, and Θ(ΔH) is the phase change activation function.

[0061] Preferably, the error function erf is expressed as:

[0062]

[0063] Where erf(x) represents the error function of parameter x; is a normalized constant, which represents the normalized control rate of the initiator addition rate; t represents the virtual time variable, is the kernel function term, which represents the fitting analysis between the free radical concentration half-life experimental data and the error function curve;

[0064] The above formula shows the kinetic characteristics of the initiator decomposition rate decaying with time, and the S-shaped curve of the error function matches the law of change of free radical concentration.

[0065] Technical effects and advantages of the present invention: Compared with traditional solid products, the chemically synthesized hot melt adhesive provided by the present invention adopts a gradient polymerization structure of styrene-butyl acrylate-methacrylic acid copolymer as the base resin, combined with the directional modification of hydroxyl / carboxylic acid functional monomers, so that the thermal stability of the material at 120°C is improved. At the same time, the molecular chain movement ability is regulated by compounding branched alkyl polyethylene wax and microcrystalline wax, so that the elongation at break of the product in a -40°C environment is improved;

[0066] The dynamic compounding of hydrogenated rosin glycerol ester and terpene resin increases the viscosity at a shear frequency of 10 rad / s compared with the single-component system, significantly improving the cohesive strength under high shear conditions; hindered phenols and phosphites are used to construct a double-layer antioxidant network in the most appropriate ratio to improve the retention rate of tensile strength;

[0067] Secondly, in terms of preparation technology, the liquid nitrogen cooling granulation process inhibits the formation of large-sized crystal areas, improves the uniformity of crystal size, and reduces the fluctuation of heat sealing strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] Figure 1 The present invention is a flow chart of the method for preparing the chemically synthesized hot melt adhesive. DETAILED DESCRIPTION

[0069] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0070] The present invention provides a formula of a chemically synthesized hot melt adhesive and a method for preparing the chemically synthesized hot melt adhesive. The prepared chemically synthesized hot melt adhesive achieves significant improvement in the physical and chemical properties of the hot melt adhesive in a wide temperature range by constructing a gradient polymerization system of a multifunctional matrix resin, developing a dynamic viscoelasticity control process, and combining high-pressure dispersion and rapid cooling technology.

[0071] The details are as follows:

[0072] A chemical synthetic hot melt adhesive, characterized in that: the formula of the chemical synthetic hot melt adhesive consists of the following ingredients:

[0073] 400-600 parts of a base resin, wherein the base resin is a vinyl copolymer with a hydroxyl or carboxylic acid functional group, and the molar ratio of the unsaturated monomer to the functional monomer in the vinyl copolymer is 3:1-5:1; the base resin is a styrene-butyl acrylate-methacrylic acid copolymer, wherein:

[0074] The styrene monomer content accounts for 45-60% of the total mass of the copolymer;

[0075] The butyl acrylate content accounts for 25-40% of the total mass of the copolymer;

[0076] The methacrylic acid content accounts for 3-8% of the total mass of the copolymer;

[0077] Its glass transition temperature is -35°C to -20°C.

[0078] In addition, the synthesis process of the base resin includes:

[0079] The three-stage polymerization process with gradient temperature control is as follows:

[0080] First polymerization stage: bulk polymerization is initiated at 65-75°C;

[0081] The second polymerization stage: heating to 85-90°C for grafting reaction;

[0082] The third polymerization stage: cooling to 70-75°C to complete the directional modification of functional groups.

[0083] 200-350 parts of a tackifier, which is composed of hydrogenated rosin glycerol ester and terpene resin in a mass ratio of 1:0.8-1:1.2; the hydrogenated rosin glycerol ester and terpene resin in the tackifier are:

[0084] The degree of hydrogenation of rosin acid is 85-95%, and the softening point of terpene resin is 105-125°C;

[0085] The composite system of the two exhibits a synergistic viscosity-increasing effect at a shear frequency of 10 rad / s, and the composite viscosity is 1.2-1.8 times that of the single component viscosity.

[0086] 80-150 parts of viscosity modifier, including a blend of polyethylene wax containing a branched alkyl structure and microcrystalline wax; the number average molecular weight of the polyethylene wax is 1500-5000, and the number of carbon atoms of the branched alkyl is 20-30; the melting point of the microcrystalline wax is 70-85°C, and the blending mass ratio of the microcrystalline wax to the polyethylene wax is 3:1-5:1.

[0087] 5-15 parts of antioxidant, wherein the antioxidant is composed of hindered phenol and phosphite compound in a ratio of 1:2-2:1; the phosphite compound is a layered silicate material, and the modification treatment of the layered silicate material includes:

[0088] First, proton exchange was performed under acidic conditions of pH 3-4;

[0089] Then, a grafting reaction is carried out with a silane coupling agent containing an epoxy group;

[0090] Finally, high temperature activation treatment is carried out at 450-550°C.

[0091] Functional additives 1-3%, including a synergistic combination of ultraviolet absorbers and inorganic fillers, wherein the ultraviolet absorbers are a composite system of hydroxybenzotriazole compounds and nano zinc oxide, and the mass ratio of the two is 1:0.5-1:1.5; the inorganic filler is a layered silicate material surface-treated with a silane coupling agent, and its particle size D50 is 2-5 μm, and the bulk density is 0.3-0.6 g / cm 3 .

[0092] In addition, this embodiment also provides a method for preparing a chemically synthesized hot melt adhesive, such as Figure 1 As shown,

[0093] The steps include:

[0094] S1, pre-reaction stage: pre-react the matrix resin raw material with a solvent at 80-100° C. for 30-60 minutes, wherein the solvent is a mixed solvent of ethyl acetate and acetone in a volume ratio of 1:0.5-1:2;

[0095] S2, main copolymerization stage: under nitrogen protection, adding a tackifier and an initiator system in sequence, wherein the initiator system comprises a gradient initiation combination of benzoyl peroxide and azobisisobutyronitrile;

[0096] Wherein, the main copolymerization stage adopts segmented temperature control:

[0097] During the heating stage, the temperature is raised to the reaction temperature at a rate of 5-8°C / min;

[0098] The temperature fluctuation during the constant temperature stage should not exceed ±1°C;

[0099] The cooling stage adopts a gradient cooling mode, including:

[0100] The first cooling stage: cooling to 100℃ at 3-5℃ / min;

[0101] The second cooling stage: cooling down to 80℃ at 1-2℃ / min;

[0102] The liquid nitrogen rapid cooling molding process comprises:

[0103] Initial cooling stage: cool the material to below -30℃ within 3-5 seconds;

[0104] Secondary shaping stage: the particle diameter is controlled in the low temperature pulverizer within the range of 0.5-2mm;

[0105] Balance treatment stage: aging for 12-24 hours at a temperature of 25℃-30℃ and a relative humidity of 40-60%;

[0106] In addition, the gradient-induced combined addition rate (v) in step S2 is performed according to the following optimization function:

[0107]

[0108] In the formula, v max represents the maximum theoretical addition rate of the initiator, erf is the error function, t 1 / 2 is the half-life correction value, ΔH obs is the heat release monitored in real time, ΔH thr is the theoretical threshold, δ is the activation buffer value, C is the catalytic transfer coefficient, and Θ(ΔH) is the phase change activation function;

[0109] The error function erf expression is:

[0110]

[0111] Where erf(x) represents the error function of parameter x; is a normalized constant, which represents the normalized control rate of the initiator addition rate; t represents the virtual time variable, is the kernel function term, which represents the fitting analysis between the free radical concentration half-life experimental data and the error function curve;

[0112] The above formula shows the kinetic characteristics of the initiator decomposition rate decaying with time, and the S-shaped curve of the error function matches the law of change of free radical concentration.

[0113] S3, functional modification stage: adding viscosity modifier three times at 110-130°C, each time with an interval of 15-30 minutes and performing ultrasonic dispersion treatment; in step S3, the interval time (Δt) of each addition of viscosity modifier is determined by the following dynamic equation:

[0114]

[0115] Where η 0 is the initial viscosity of the system (mPa·s), which was measured by rotational rheometer at 100 s -1 Measured at shear rate; η 1 is the real-time dynamic viscosity (mPa·s), collected every 30 seconds by an online viscosity sensor;

[0116] Where, ΔT = Tm-Tc;

[0117] Tm is the set upper limit of process temperature (°C);

[0118] Tc is the current material center temperature (℃);

[0119] K is the process coefficient, with a range of 8.5×10 -3 -1.2×10 -2 ;

[0120] When the calculated value exceeds the 15-30 minute range required by the process, the system automatically adjusts the ultrasonic power to:

[0121]

[0122] Where P 0 is the preset ultrasonic power, γ = 0.15 ± 0.02 is the adjustment gain, τ = (5 ± 0.5) min is the time constant, and the arctan function is limited to the interval [-π / 2, π / 2] to ensure stable output.

[0123] S4, post-processing stage: liquid nitrogen is used to quickly cool the shape after melt extrusion, and the cooling rate is controlled at 15-25℃ / s;

[0124] Among them, the oxygen content of the whole process of the preparation method of chemical synthetic hot melt adhesive is controlled below 50ppm.

[0125] In summary, the matrix resin of the present invention adopts a gradient polymerization structure of styrene-butyl acrylate-methacrylic acid copolymer, combined with directional modification of hydroxyl / carboxylic acid functional monomers, so that the thermal stability of the material at 120°C is improved. At the same time, the molecular chain mobility is regulated by compounding branched alkyl polyethylene wax and microcrystalline wax, so that the elongation at break of the product in a -40°C environment is improved;

[0126] The dynamic compounding of hydrogenated rosin glycerol ester and terpene resin increases the viscosity at a shear frequency of 10 rad / s compared with the single-component system, significantly improving the cohesive strength under high shear conditions; hindered phenols and phosphites are used to construct a double-layer antioxidant network in the most appropriate ratio to improve the retention rate of tensile strength;

[0127] Secondly, in terms of preparation technology, the liquid nitrogen cooling granulation process inhibits the formation of large-sized crystal areas, improves the uniformity of crystal size, and reduces the fluctuation of heat sealing strength.

[0128] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A chemically synthesized hot melt adhesive, characterized in that: The formula of the chemically synthesized hot melt adhesive consists of the following ingredients: 400-600 parts of a base resin, wherein the base resin is a vinyl copolymer with a hydroxyl or carboxylic acid functional group, and the molar ratio of the unsaturated monomer to the functional monomer in the vinyl copolymer is 3:1-5:1; 200-350 parts of a tackifier, which is prepared by mixing hydrogenated rosin glycerol ester and terpene resin in a mass ratio of 1:0.8-1:1.2; 80-150 parts of a viscosity modifier, comprising a blend of polyethylene wax containing a branched alkyl structure and microcrystalline wax; 5-15 parts of an antioxidant, wherein the antioxidant is composed of a hindered phenol and a phosphite compound in a ratio of 1:2-2:1; Functional additives 1-3%, including a synergistic combination of ultraviolet absorbers and inorganic fillers, wherein the ultraviolet absorbers are a composite system of hydroxybenzotriazole compounds and nano zinc oxide, and the mass ratio of the two is 1:0.5-1:1.5; the inorganic filler is a layered silicate material surface-treated with a silane coupling agent, and its particle size D50 is 2-5 μm, and the bulk density is 0.3-0.6 g / cm 3 .

2. A chemically synthesized hot melt adhesive according to claim 1, characterized in that: The base resin is styrene-butyl acrylate-methacrylic acid copolymer, wherein: The styrene monomer content accounts for 45-60% of the total mass of the copolymer; The butyl acrylate content accounts for 25-40% of the total mass of the copolymer; The methacrylic acid content accounts for 3-8% of the total mass of the copolymer; Its glass transition temperature is -35°C to -20°C.

3. A chemically synthesized hot melt adhesive according to claim 2, characterized in that: The synthesis process of the base resin includes: The three-stage polymerization process with gradient temperature control is as follows: First polymerization stage: bulk polymerization is initiated at 65-75°C; Second polymerization stage: heating to 85-90℃ for grafting reaction; The third polymerization stage: cooling to 70-75°C to complete the directional modification of functional groups.

4. The chemical synthetic hot melt adhesive according to claim 1, characterized in that: The synthesis process of the base resin includes: the hydrogenated rosin glycerol ester of the tackifier and the terpene resin: The degree of hydrogenation of rosin acid is 85-95%, and the softening point of terpene resin is 105-125°C; The composite system of the two exhibits a synergistic viscosity-increasing effect at a shear frequency of 10 rad / s, and the composite viscosity is 1.2-1.8 times that of the single component viscosity.

5. A method for preparing the chemically synthesized hot melt adhesive according to claim 1, characterized in that: The steps include: S1, pre-reaction stage: pre-react the matrix resin raw material with a solvent at 80-100° C. for 30-60 minutes, wherein the solvent is a mixed solvent of ethyl acetate and acetone in a volume ratio of 1:0.5-1:2; S2, main copolymerization stage: under nitrogen protection, adding a tackifier and an initiator system in sequence, wherein the initiator system comprises a gradient initiation combination of benzoyl peroxide and azobisisobutyronitrile; S3, functional modification stage: adding viscosity modifier three times at 110-130°C, each time with an interval of 15-30 minutes and performing ultrasonic dispersion treatment; S4, post-processing stage: liquid nitrogen is used to quickly cool the shape after melt extrusion, and the cooling rate is controlled at 15-25℃ / s; Among them, the oxygen content of the whole process of the preparation method of chemical synthetic hot melt adhesive is controlled below 50ppm.

6. The method for preparing a chemically synthesized hot melt adhesive according to claim 5, characterized in that: The main copolymerization stage adopts segmented temperature control: During the heating stage, the temperature is raised to the reaction temperature at a rate of 5-8°C / min; The temperature fluctuation during the constant temperature stage should not exceed ±1°C; The cooling stage adopts a gradient cooling mode, including: The first cooling stage: cooling to 100℃ at 3-5℃ / min; The second cooling stage: cooling down to 80℃ at 1-2℃ / min; The liquid nitrogen rapid cooling molding process comprises: Initial cooling stage: cool the material to below -30℃ within 3-5 seconds; Secondary shaping stage: the particle diameter is controlled in the low temperature pulverizer within the range of 0.5-2mm; Balance treatment stage: aging for 12-24 hours at a temperature of 25°C-30°C and a relative humidity of 40-60%.

7. The method for preparing a chemically synthesized hot melt adhesive according to claim 5, characterized in that: In step S3, the interval time (Δt) of adding the viscosity modifier each time is determined by the following dynamic equation: Where η0 is the initial viscosity of the system (mPa·s), which is measured by a rotational rheometer at 100s. -1 Measured at shear rate; η1 is the real-time dynamic viscosity (mPa·s), which is collected every 30 seconds by an online viscosity sensor; Where, ΔT = Tm-Tc; Tm is the set upper limit of process temperature (°C); Tc is the current material center temperature (℃); K is the process coefficient, with a range of 8.5×10 -3 -1.2×10 -2 ; When the calculated value exceeds the 15-30 minute range required by the process, the system automatically adjusts the ultrasonic power to: Where P0 is the preset ultrasonic power, γ = 0.15 ± 0.02 is the adjustment gain, τ = (5 ± 0.5) min is the time constant, and the arctan function is limited to the interval [-π / 2, π / 2] to ensure output stability.

8. The method for preparing a chemically synthesized hot melt adhesive according to claim 5, characterized in that: The gradient-induced combined addition rate (v) in step S2 is performed according to the following optimization function: In the formula, v max represents the maximum theoretical addition rate of the initiator, erf is the error function, t 1 / 2 is the half-life correction value, ΔH obs is the heat release monitored in real time, ΔH thr is the theoretical threshold, δ is the activation buffer value, C is the catalytic transfer coefficient, and Θ(ΔH) is the phase change activation function.

9. The method for preparing a chemically synthesized hot melt adhesive according to claim 8, characterized in that: The error function erf expression is: Where erf(x) represents the error function of parameter x; is a normalized constant, which represents the normalized control rate of the initiator addition rate; t represents the virtual time variable, is the kernel function term, which represents the fitting analysis between the free radical concentration half-life experimental data and the error function curve; The above formula shows the kinetic characteristics of the initiator decomposition rate decaying with time, and the S-shaped curve of the error function matches the law of change of free radical concentration.

Citation Information

Cited By

  • Solar cell copper electrode composite current collector and preparation method thereof

    CN122138477A

  • A copper electrode composite current collector for solar cells and its preparation method

    CN122138477B